Gastroscopy-related adverse cardiac events and bleeding complications among patients treated with coronary stents and dual antiplatelet therapy - Egholm, Gro; Thim, Troels; Madsen, Morten; Sørensen, Henrik Toft; Pedersen, Jan Bech; Eggert Jensen, Svend; Jensen, Lisette Okkels; Kristensen, Steen Dalby; Bøtker, Hans Erik; Maeng, Michael (Endoscopy International Open, 2016)
Background and study aims: Dual antiplatelet therapy (DAPT) is recommended following percutaneous coronary intervention (PCI) with drug-eluting stent (DES). DAPT is a risk factor for gastrointestinal bleeding. We aimed to quantify (1) the rate of gastroscopy within 12 months after PCI, (2) the rate of adverse cardiac events and gastroscopy-related bleeding complications within 30 days of gastroscopy, and (3) the association between antiplatelet therapy and these events.Patients and methods: Patients receiving gastroscopy within 12 months of PCI were identified and two nested case-control analyses were performed within the PCI cohort by linking Danish medical registries. Cases were patients with adverse cardiac events (cardiac death, myocardial infarction, or stent thrombosis) or hemostatic intervention. In both studies, controls were patients with gastroscopy including biopsy without adverse cardiac events and hemostatic intervention, respectively. Medical records were reviewed to obtain information on exposure to DAPT.Results: We identified 22 654 PCI patients of whom 1497 patients (6.6 %) underwent gastroscopy. Twenty-two patients (1.5 %) suffered an adverse cardiac event, 93 patients (6.2 %) received hemostatic intervention during or within 30 days of the index gastroscopy. Interrupting DAPT was associated with a 3.46 times higher risk of adverse cardiac events (95 %CI 0.49 – 24.7). Discontinuation of one antiplatelet agent did not increase the risk (OR 0.65, 95 %CI 0.17 – 2.47). No hemostatic interventions were caused by endoscopic complications.Conclusion: Gastroscopy can be safely performed in PCI patients treated with DES and single antiplatelet therapy while interruption of DAPT may be associated with an increased risk of adverse cardiac events.